2021
DOI: 10.2147/jmdh.s320243
|View full text |Cite
|
Sign up to set email alerts
|

Change-Event Steals “Athlete” from “College Athlete”: Perceived Impact and Depression, Anxiety, and Stress

Abstract: Introduction: This research sought to establish the impact of the change-event of COVID-19 on college athletes and members of other campus groups (eg, marching band, eSports, Reserve Officers Training Corps). The specific purpose was to assess the perceived impact and impact on mental health (eg, depression, anxiety, and stress). Methods: The survey battery presented a total of 37 items. Demographic, sport or groupspecific, and academic-related questions were included alongside the assessment of psychological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Twenty-four of the 32 studies § § assessed athlete mental health at a single time point during the lockdown. This included measurements of the severity and/or prevalence of depression, | || | anxiety, {{ stress, 12,16,17,29,38,39,48,51 motivation, 42,47 hyperarousal, 12,16 and insomnia, 39,40 among others. Ha ˚kansson et al 24 found that 66% of athletes expressed worry about the future of their sport and 51% about their future playing sports.…”
Section: Effect Of Covid-19 Lockdownmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-four of the 32 studies § § assessed athlete mental health at a single time point during the lockdown. This included measurements of the severity and/or prevalence of depression, | || | anxiety, {{ stress, 12,16,17,29,38,39,48,51 motivation, 42,47 hyperarousal, 12,16 and insomnia, 39,40 among others. Ha ˚kansson et al 24 found that 66% of athletes expressed worry about the future of their sport and 51% about their future playing sports.…”
Section: Effect Of Covid-19 Lockdownmentioning
confidence: 99%
“…Ha ˚kansson et al 24 found that 66% of athletes expressed worry about the future of their sport and 51% about their future playing sports. Depression was reported Davila-Torres et al 9 U a Denerel et al 11 U a U dI Cagno et al 12 U a U U U Facer-Childs et al 14 U a Fiorilli et al 16 U a U U U U Garver et al 17 U a U Gouttebarge et al 19 U U U Graupensperger et al 20 U Hagiwara et al 23 U a U Ha ˚kansson et al 24 U a U U Jagim et al 26 U a Knowles et al 27 U a U Leguizamo et al 29 U Martı ´nez-Gonza ´lez et al 30 U McGuine et al 31 U a U U U Mehrsafar et al 33 U a Melnyk et al 34 U a U U Mon-Lo ´pez et al 35 U a U Ozen et al 38 U a Parm et al 39 U a U Pensgaard et al 40 U a U U U Pillay et al 42 U a U Pons et al 43 U a U U Roberts and Lane 45 U Rubio et al 46 U a U U Ruffault et al 47 U a U U U S xenıs xık et al 48 U a Simons et al 49 U Soares et al 50 U a Vaughan et al 51 U in 19% of women and 3% of men, and anxiety in 20% of women and 5% of men. Likewise, two-thirds of athletes in the Parm et al 39 study exhibited distress, with 39.7% of women and 25% of men experiencing depressive symptoms, and 27.6% of women and 13.6% of men demonstrating anxiety.…”
Section: Effect Of Covid-19 Lockdownmentioning
confidence: 99%
“…Altogether, limited research has sampled young student-athletes with attention to mental health during the COVID-19 pandemic (Batalla-Gavalda et al, 2021 ; Conde et al, 2021 ; Garver et al, 2021 ; McGuine et al, 2021 ). Therefore, the present study aimed to examine mental health parameters in a cohort of student-athletes, within a nation-wide elite sport high school system in Sweden, during the COVID-19 pandemic, including the subjective impact on mental health and worry about the future of their sports and their own future in their sport, clinical ratings of depression and anxiety, and behavioral changes related to video gaming behavior.…”
Section: Introductionmentioning
confidence: 99%
“…This is not surprising. Depressive symptoms are known to be more common among women than men ( 62 ); however, the difference is usually not significant among university students and student-athletes ( 4 , 63 ). Gender differences were significant in this study, but the difference in the risk of having important level of depressive symptoms was quite small.…”
Section: Discussionmentioning
confidence: 99%